1976
DOI: 10.1111/j.1365-2621.1976.tb00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycoalkaloids and Phenolics on Potato Flavor

Abstract: The principles of the flavor profile method were used to establish the relationship between the flavor of potatoes and their total glycoalkaloid and total phenol& contents. Tuber tissues from the seven potato clones that had glycoalkaloid contents in excess of 14 mg/lOOg were rated as bitter by the taste panel. The correlation between glycoalkaloid contents and bitterness ratings for the 13 clones included in the study was highly significant (r = 0.93). Tissues that had glycoaikaloid contents in excess of 22 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
2
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(77 citation statements)
references
References 10 publications
1
73
2
1
Order By: Relevance
“…The Aymara population actually most preferred a potato variety with as much as 17 mg/100 g total glyqoalkaloids. The present experiment is not directly comparable to that carried out by Sinden et al (1976), but these two results are not greatly different. The difference suggests that the Aymara have a slightly higher threshold level of response to glycoalkaloid content.…”
Section: Glycoalkaloid Content and Potato Taste Qualitycontrasting
confidence: 49%
See 1 more Smart Citation
“…The Aymara population actually most preferred a potato variety with as much as 17 mg/100 g total glyqoalkaloids. The present experiment is not directly comparable to that carried out by Sinden et al (1976), but these two results are not greatly different. The difference suggests that the Aymara have a slightly higher threshold level of response to glycoalkaloid content.…”
Section: Glycoalkaloid Content and Potato Taste Qualitycontrasting
confidence: 49%
“…The characteristic flavor of potatoes results from a complex interaction of free amino acids, 5'-nucleotides, simple sugars, phenolics, and glycoalkaloids (Solms and Wyler, 1979;Sinden, Deahl, and Aulenbach, 1976). Of interest in this study are the bitter and potentially toxic glycoalkaloids.…”
Section: Glycoalkaloids and Potato Taste Qualitymentioning
confidence: 99%
“…alpha-solanine and alpha-chaconine) in tubers as quality trait in potato has received considerable attention. These alkaloids impart a bitter flavour to potatoes (Sinden et al 1976), and most importantly they are toxic to humans (McMillan and Thompson 1979). Furthermore, accumulation of glycoalkaloids was associated with the greening of tubers (Maga and Fitzpatrick 1980), although a direct link between the two processes has not been proven (Gull and Isenberg 1960).…”
Section: Potato (Solanum Tuberosum L)mentioning
confidence: 99%
“…1) are detected in tissues of tubers except in the pith or center portion (Maga, 1980). It has been reported that these glycoalkaloids show acute toxicity (Jellema et al, 1980; McMillan & Thompson, 1980), chronic toxicity (Mun et al, 1975;Keeler et al, 1976), and have a bitter taste (Sinden & Deahl, 1976; Woolfe, 1987). The intrinsic glycoalkaloid content in tubers of commercial potato cultivars is low due to selection in breeding, but the content may increase in response to environmental stress conditions, such as light (Friedman, 1997;Griffiths et al, 1994;Kozukue et al, 1993;Maga, 1980;Percival & Dixon, 1994;Percival, 1999; Sinden et al, 1984; Woolfe, 1987), frost and hail damage, and wounding during harvesting or postharvest handling (Woolfe, 1987).…”
Section: Introductionmentioning
confidence: 99%